Best Answer

I am assuming that k is the constant of proportionality so that

f = k*a*t/b2 = 3*4*6/22 = 18

Study guides

☆☆

Q: When f varies jointly as a and t and inversely as the square of b what is the answer when determining f when k equals 3 a equals 4 t equals 6 and b equals 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

25

y varies inversely as x2 so y = c/x2 for some constant c. When x = 5, y = 4 So c = x2y = 100 that is y = 100/x2 Then, when x = 2, y = 100/4 = 25

Graham's law of effusion.

It is the square root of 10 times the square root of 10 equals 10

It is: the square root of 185 times the square root of 185 equals 185

Related questions

I'm pretty sure the answer is: C= de3k/ √m (C equals d times e cubed times k, divided by the square root of m).

25

C = k*a*d*e^3/sqrt(m) where k is a constant.

The gravity is proportional to both masses involved, and inversely proportional to the square of the distance.The gravity is proportional to both masses involved, and inversely proportional to the square of the distance.The gravity is proportional to both masses involved, and inversely proportional to the square of the distance.The gravity is proportional to both masses involved, and inversely proportional to the square of the distance.

By a factor of 9. Gravitational force is inversely proportional to the square of the distance.By a factor of 9. Gravitational force is inversely proportional to the square of the distance.By a factor of 9. Gravitational force is inversely proportional to the square of the distance.By a factor of 9. Gravitational force is inversely proportional to the square of the distance.

No. The word is "inversely", not "conversely". And the force of gravity is inversely proportional to the square of the distance.

x2y = k (constant) so 36 x 2 ie 72 is the constant. If x = 3 then y = 72/9 = 8

The statement "y varies inversely as the square of x" means that in function form y(x) = k/x2, where k is an (initially) unknown constant. The second condition can be written in algebraic form as 4 = k/32 ; or k = 4 X 9 = 36; Then y(2) = 36/22 = 9.

y varies inversely as x2 so y = c/x2 for some constant c. When x = 5, y = 4 So c = x2y = 100 that is y = 100/x2 Then, when x = 2, y = 100/4 = 25

X=k/square of y

The amount of illumination is inversely proportional to the distance from the light source. In general, the inverse-square law states that the power intensity of an expanding wave is inversely proportional to the square of the distance from the source. i.e. Intensity  1 / Distance2

The law is called The Inverse Square Law .

People also asked

Featured Questions